



 
Ho Symion, For this problem I would use the distributive property which says that \[a (b + c) = a b + a c\] or written with the multiplication on the right \[(d + e) f = d f + e f.\] I am going to illustrate with two problems similar to yours.
To apply the distributive law think of $(x  3)$ as $a$ and you get \[(x  3) (x + 2) = (x  3) \times x + (x  3) \times 2.\] Now apply the distributive law with the multiplication on the right to get \[(x  3) \times x + (x  3) \times 2 = x \times x + (3) \times x + x \times 2 + (3) \times 2.\] Collecting like terms results in \[(x  3)(x + 2) = x^2 x 6.\] For a second example
Using the same technique I uses for the first example \[(x + 5) (x + 5) = (x + 5) \times x + (x + 5) \times 5 = x \times x + 5 \times x + x \times 5 + 5 \times 5\] which simplifies to \[(x + 5)(x + 5) = x^2 + 10 x + 25.\] Now try your problem,  


Math Central is supported by the University of Regina and the Imperial Oil Foundation. 